Fat body disintegration after freezing stress is a consequence rather than a cause of freezing injury in larvae of Drosophila melanogaster. (May 2019) - Rozsypal, Jan; Toxopeus, Jantina; Berková, Petra; Moos, Martin; Šimek, Petr; Koštál, Vladimír
Graphical abstract: Highlights: Fat body tissue of frozen larvae of Drosophila melanogaster rapidly disintegrates. Fat body disintegration is a consequence rather than a cause of freezing injury. Feeding larvae proline-augmented diet mitigates fat body disintegration. Induction of low-temperature quiescence mitigates fat body disintegration. Mitigation of damage is associated with changes in membrane composition. Abstract: Extracellular freezing of insect body water may cause lethal injury either by direct mechanical stress exerted by growing ice crystals on cells and tissues or, indirectly, by deleterious physico-chemical effects linked to freeze-induced cell dehydration. Here we present results showing that the macroscopic damage (cell ruptures, tissue disintegration) to fat body of Drosophila melanogaster is not directly caused by mechanical forces linked to growth of ice crystals but rather represents a secondary consequence of other primary freeze injuries occurring at subcellular or microscopic levels. Larvae of D. melanogaster were acclimated to produce variants ranging from freeze susceptible to freeze tolerant. Then, larvae were exposed to supercooling and freezing stresses at different subzero temperatures. The larval survival and macroscopic damage to fat body tissue was scored in 1632 larvae exposed to cold stress. In most cases, fat body damage was not evident immediately following cold stress but developed later. This suggests that the fat body disintegration is a consequence rather than a cause of cold injury. Analysis of fat body membrane phospholipids revealed that increased freeze tolerance was associated with increased relative proportion of phosphatidylethanolamines (PEs) at the expense of phosphatidylcholines (PCs). The PE/PC ratio increased from 1.08 in freeze-susceptible larvae to 2.10 in freeze-tolerant larvae. The potential effects of changing PE/PC ratio on phospholipid bilayer stability upon supercooling and freezing stress are discussed.